The Prevalence and The Association of Antibiotic Practices with Surgical Site Infection Following Cesarean Section - Hussein, Maiga Ayub; Sutiningsih, Dwi; Ntambi, Saidi; Frida, Chebet (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: This study focuses on Cesarean section (CS) procedures and the associated risk of surgical site infections (SSIs). The global CS rate is currently at 21%, higher than the recommended 15%, leading to an increased risk of SSIs. These infections are a significant burden on economies, healthcare systems, patients, and their families, despite being preventable. The research aims to address the issue in Uganda, where the burden of SSIs stands at 15.5%. While previous studies have examined various risk factors, such as age, parity, surgeon expertise, and antiseptic solutions, there is a lack of research on pre- and post-CS antibiotic practices and their connection to SSIs. This study seeks to establish the prevalence of SSIs and evaluate the antibiotic practices before and after CS procedures at Mbale Regional Referral Hospital from January 1, 2020, to December 31, 2022.Methods: The design was retrospective cross-sectional. Consecutively selected 104 patient files that developed SSIs and randomly an equal number of patient files that did not develop SSIs to make up a sample size of 208 files that were reviewed at Mbale regional referral hospital (MRRH) from 1st –January -2020 to 31st -December-2022.Result: The prevalence of surgical site infections (SSIs) was 4.3%. Among the 208 patient files reviewed, 71.2% received antibiotic prophylaxis, with intravenous ceftriaxone being the most common (47.1%). However, only 14.9% received prophylaxis within the recommended 30-60 minutes before incision. Post-cesarean section, 92.8% received intravenous ceftriaxone and metronidazole, and the mean hospital stay was 2.74 days. Factors significantly associated with reduced SSI risk were the timing of antibiotic prophylaxis, administration of intravenous antibiotics post-cesarean, oral antibiotics post-cesarean, duration of hospital stay, and the cadre of the surgeonConclusion: The prevalence of surgical site infections (SSIs) at Mbale Regional Referral Hospital (MRRH) was found to be 4.3%. This study highlighted several factors that were associated with a reduced risk of SSIs in women undergoing Cesarean section (CS), including timely administration of antibiotic prophylaxis within 30-60 minutes before the incision, the use of post-CS intravenous (IV) ceftriaxone and metronidazole, hospital stays of 3 days, oral cefixime upon discharge, and being operated on by a medical officerRecommendation: The study emphasizes the importance of medical professionals following guidelines and acquiring knowledge on appropriate antibiotic use to combat surgical site infections (SSIs) following cesarean sections. Adhering to guidelines and continuous education is crucial in preventing SSIs and addressing antibiotic resistance